P148 Timing to surgery in symptomatic Crohn's disease—patients perception. (25th January 2019) - Moratal, M; Marti-Gallostra, M; Vallribera, F; Epín, E
Abstract: Background: Medical treatment is still the first approach on Crohn's disease (CD) in most of the cases. Patients on remission after medical and/or surgical treatment show significant improvement on their quality of life (QoL). However, there is scarce bibliography evaluating the patients point of view regarding their surgery and the timing on performing this. The aim of this study was to evaluate how confident are patients with the timing of their surgery and how the surgery changed their QoL. Methods: A questionnaire was sent to 274 patients operated, as a first surgery, between 1989 to 2018 due to CD at a single institution. The questionnaire included 12 questions: evaluating if they would have preferred their surgery (with or without stoma) to have been carried out sooner, later or at the same time as it was done and about their changes in quality of life. Clavien Dindo's classification was used to evaluate postoperative complications. A consent form was obtained from all patients participating on the study. The study was accepted by our Ethics Committee. Results: In total, 98 (36%) patients complete the questionnaire. Seventy-two of 98 had a CD location type L1, 14/98 L2 and 12/98 L3. The behaviour of CD was 5 B1; 56 B2; and 37 B3. A stoma was done in 16 patients. Twenty-five patients needed a reintervention due to a relapse of the disease. Eighty of 98 reported a significant improvement in their QoL after their first surgery; 11/98 did not experience any change, and 7/98 explained a drop on it. Analysing the group of patients that needed a stoma as a treatment: 12/16 (75%) reported an improvement in their QoL; 2/16 (12%) did not experience changes and 2 more explain a worsen on it. Regarding the timing on surgery: 30/98 preferred their operation to have been done earlier (8/30 (26%) experienced some postoperative complication); and 6/98 thought it should have been done later. Ninety-three of 98 patient will accept a new surgery if the disease would reappear, and of them 33/93 (35%) had postoperative complications after surgery. Conclusions: Surgery for CD improves patients QoL in a high proportion of patients even on those that need a stoma. One on every three patients in this series preferred their operation to have been done earlier. More studies should be done to consider if earlier surgery should be offered as an alternative to medical treatment rather than as an option when medical treatment fails.